Autophagosome content profiling reveals receptor-specific cargo candidates. Issue 5 (4th May 2021) - Zellner, Susanne; Behrends, Christian
ABSTRACT: Selective autophagy receptors have been implicated in the degradation of cellular constituents of various size and rigidity. However, the identity of protein cargo have largely remained elusive. In our recent study, we combined limited proteolysis-enhanced proximity biotinylation and organelle enrichment with quantitative proteomics to map the inventory of autophagosomes in a manner dependent on six different selective autophagy receptors, namely SQSTM1/p62, NBR1, CALCOCO2/NDP52, OPTN, TAX1BP1 and TOLLIP. Conducting this approach under basal and proteostasis-challenged conditions in mammalian cells led to the identification of various new autophagy substrates of which some were degraded through endosomal microautophagy rather than canonical autophagy dependent on the receptors TOLLIP and SQSTM1, respectively.